Implementasi PERMA No. 2 Tahun 2015 di Pengadilan Negeri Yogyakarta - Bambang Sutiyoso; Ayu Atika Dewi; Fuadi Isnawan (Fakultas Hukum Universitas Islam Indonesia, 2019)
o overcome the barriers in the dispute settlement in court, the Supreme Court issued a new mechanism for the settlement of civil cases, called as simple civil claims. The procedure mechanism was introduced through the issuance of PERMA No. 2 of 2015 concerning Simple Civil Claim. The researcher in this study intended to observe the implementation of the PERMA of Simple Civil Claim in Yogyakarta DistrictCourt, along with the obstacles. The study was conducted using the empirical juridical research methodand analytical descriptive data analysis. From the research results, it can be concluded that the implementation of PERMA No. 2 of 2015 concerning Simple Civil Claim in Yogyakarta District Court is still ineffective in practice. This has been determined by various factors such as the rule of law, legal officers, facilities and infrastructure and community. The researcher also found a number of obstaclesfaced in implementing PERMA, some of which were related to the existence of options to choose the procedure mechanism, tight case qualifications that could be submitted through simple program procedures and lack of PERMA socialization.